Chaperone function in antigen presentation by MHC class I molecules—tapasin in the PLC and TAPBPR beyond - Margulies, David H.; Jiang, Jiansheng; Ahmad, Javeed; Boyd, Lisa F.; Natarajan, Kannan (Frontiers in Immunology, 2023)
Peptide loading of MHC-I molecules plays a critical role in the T cell response to infections and tumors as well as to interactions with inhibitory receptors on natural killer (NK) cells. To facilitate and optimize peptide acquisition, vertebrates have evolved specialized chaperones to stabilize MHC-I molecules during their biosynthesis and to catalyze peptide exchange favoring high affinity or optimal peptides to permit transport to the cell surface where stable peptide/MHC-I (pMHC-I) complexes are displayed and are available for interaction with T cell receptors and any of a host of inhibitory receptors. Although components of the endoplasmic reticulum resident peptide loading complex (PLC) were identified some 30 years ago, the detailed biophysical parameters that govern peptide selection, binding, and surface display have only recently been determined as advances in structural methods including X-ray crystallography, cryo-electron microscopy (cryoEM) and computational modeling, have provided refined mechanistic illustration of the molecular events involved in the folding of the MHC-I heavy chain, its coordinate glycosylation, assembly with its light chain, 2-microglobulin (2m), its association with the peptide loading complex (PLC), and its binding of peptides. Our current view of this important cellular process as it relates to antigen presentation to CD8 T cells is based on many different approaches: biochemical, genetic, structural, computational, cell biological, and immunological. In this review, taking advantage of recent X-ray and cryoEM structural evidence and molecular dynamics simulations, examined in the context of past experiments, we attempt a dispassionate evaluation of the details of peptide loading in the MHC-I pathway. By critical evaluation of several decades of investigation, we outline aspects of the peptide loading process that are well-understood, and those that demand further detailed investigation. Further studies should contribute not only to basic understanding, but also to applications for immunization and therapy of tumors and infections.